Potential Anti-Cancer Properties of Bacteriocin UL4 from Lactobacillus Plantarum in Rats Induced with Colon Cancer - Muhamad Zakuan, Noraina (2011)
Colorectal cancer (CRC) is the fourth and the third most common cancer in men and women worldwide, respectively. Despite improvements in the treatment modalities of CRC such as surgery, radiotherapy and chemotherapy, all of them especially chemotherapy can result in severe side effects. Thus, more specific and effective treatment needs to be developed to improve and add to the available ones. Currently, much attention has been directed towards the development of natural or natural product-based anticancer agents that are believed to have lesser side effects. Among those are probiotics and their metabolites, and prebiotics. Bacteriocin UL4 (UL4) is a metabolite from Lactobacillus plantarum that showed antitumor promoting activities in mice induced with skin cancer. It was also demonstrated that postweaning rats fed with UL4 had a lower blood cholesterol concentration. This study was carried out not only to determine the anti-colorectal cancer properties of UL4, but also its immunomodulatory activities. Briefly,Sprague Dawley male rats were injected subcutaneously with azoxymethane (AOM) for two subsequent weeks (15mg/kg/week) to induce colorectal cancer. The animals were fed with different percentages of UL4 (0.25%, 0.5% and 0.75% of UL4 (w/w)) added into drinking water at week 26, once daily for 12 weeks. The positive (with cancer) and negative control group (normal rats, without cancer) were also included. Upon completion, the animals were sacrificed. The colon, spleen and thymus were removed. Immune cell suspensions were prepared from spleen and thymus of rats. The regional distribution of aberrant crypt foci (ACF) at the proximal, medial and distal part was histopathologically evaluated following hematoxylin and eosin staining. In further classification of ACF into hyperplasia without dysplasia, mild to moderate dysplasia and severe dysplasia, the number of ACF in all classifications reduced significantly in group treated with 0.5 and 0.75% of UL4 as compared to the PC group. The incidence of tumor was also found to decrease significantly in all UL4-treated groups as compared to the PC group (p>0.05). In concordance with the reduced incidence of ACF and tumor, expression of ß-catenin decreased significantly in all UL4-treated groups as compared to PC group. Results showed that effects of UL4 on the incidence of tumor and on the expression of ß-catenin were dose-independent. The immunomodulatory properties of UL4 were determined based on the level of several cytokines (IFN-γ, TNF-α, IL-12 and IL-5). The level of studied cytokines (IFN-γ, TNF-α and IL-5) except for IL-12 in serum, increased significantly (p<0.05) in all UL4-treated groups as compared to the PC group. In general, the level of cytokines studied (IFN-γ, TNF-α, IL-12 and IL-5) increased significantly in groups treated with 0.5% and 0.75% of UL4 in both spleen and thymus cells as compared to the PC group. Effects of UL4 on the level of studied cytokines seem to be dose-independent. As a conclusion, UL4 reduced the number of tumor and the expression of β-catenin in rats induced with colorectal cancer. UL4 also enhanced the production of IFN-γ, TNF-α, IL-12 and IL-5, the cytokines that are crucially involved and play a significant role in inhibition of colon carcinogenesis. Therefore, UL4 has potential as an anti-colorectal cancer agent possibly by modulating the immune responses of patients to fight cancer.